The Bhagavad Gita: A Central Cultural Asset of Indian Nationalism - Khatri, Tilak Bahadur (Cognition, 2021)
This research article deals with the commentary of the Bhagavad Gita in the post-independent period of India. The study has its relevance to understand the status of the text in this period. The article addresses on the research problems concerning to worldwide scholarly commentaries of the text in this period. The research approach adopted for this study is the review-based analysis of the text’s commentaries of different scholars of the time. The study reveals that the most of the commentators of the Gita highly praise the text and establish it as the central cultural asset of Indian nationalism.